Characteristics, treatment and outcomes of nontuberculous mycobacterial pulmonary disease after allogeneic haematopoietic stem cell transplant. Issue 5 (3rd May 2018) - Hirama, Takashi; Brode, Sarah K.; Beswick, Jenifer; Law, Arjun D.; Lam, Wilson; Michelis, Fotios V.; Thyagu, Santhosh; Viswabandya, Auro; Lipton, Jeffrey H.; Messner, Hans A.; Kim, Dennis (Dong Hwan); Marras, Theodore K.
Allogeneic haematopoietic stem cell transplant (alloHCT) recipients are at risk for a variety of opportunistic infections. While typical bacterial infections occur most frequently, nontuberculous mycobacteria (NTM) are becoming increasingly recognised as pathogens after alloHCT [1]. The prevalence of NTM pulmonary disease (NTM-PD) is increasing worldwide, with a rise in Ontario's period prevalence from 29.3 per 100 000 in 1998–2002 to 41.3 per 100 000 in 2006–2010 [2]. Likewise, the incidence of NTM-PD post alloHCT increased from 0.11–0.23% [3, 4] in early studies to 2.7–3.15% in recent investigations [5, 6]. Despite the incidence of NTM-PD after alloHCT being far higher than in the general population [6], there are few reports addressing management and treatment outcomes of NTM-PD after alloHCT. We reviewed the experience with NTM-PD among alloHCT recipients at our institution to better characterise clinical features and treatment outcomes. Nontuberculous mycobacterial pulmonary disease in allogeneic haematopoietic stem cell transplant recipients http://ow.ly/5epj30j6bfy